The Role of Norrish Type-I Chemistry in Photoactive Drugs: An ab initio Study of a Cyclopropenone-Enediyne Drug Precursor - Léger, Spencer J.; Marchetti, Barbara; Ashfold, Michael N. R.; Karsili, Tolga N. V. (Frontiers in Chemistry, 2020)
We present a contemporary mechanistic description of the light-driven conversion of cyclopropenone containing enediyne (CPE) precusors to ring-opened biradical species amenable to further Bergman cyclization and formation of stable biradical species that have been proposed for use in light-induced cancer treatment. The transformation is rationalized in terms of (purely singlet state) Norrish type-I chemistry, wherein photoinduced opening of one C–C bond in the cyclopropenone ring facilitates non-adiabatic coupling to high levels of the ground state, subsequent loss of CO and Bergman cyclization of the enediyne intermediate to the cytotoxic target biradical species. Limited investigations of substituent effects on the ensuing photochemistry serve to vindicate the experimental choices of Popik and coworkers (J. Org. Chem., 2005, 70, 1297–1305). Specifically, replacing the phenyl moiety in the chosen model CPE by a 1,4-benzoquinone unit leads to a stronger, red-shifted parent absorption, and increases the exoergicity of the parent biradical conversion.